How party nationalization conditions economic voting. (June 2017) - Morgenstern, Scott; Smith, Noah; Trelles, Alejandro
Abstract: In this article we analyze the conditioning effect of party nationalization, and in particular dynamic nationalization, on economic voting. While previous single-country and cross-national studies suggest a weak correlation between economic conditions and voting patterns, we argue that this relationship is conditioned by the degree to which parties are dynamically nationalized. Using both case study and large-n analysis, we show first that retrospective voting can be more nationalized than prospective voting. We then argue that national economic conditions cannot and do not relate to voting patterns, at least when weak dynamic nationalization is weak. The findings also call into question the well-known thesis about the clarity of responsibility as a conditional factor in explaining retrospective (economic) voting. There is imperfect correspondence between "clarity of responsibility" and dynamic party nationalization, but retrospective voting presumes that voters across the country respond in kind. This explains why the only evidence we find of a correlation of national economic indicators and voting is when there is high dynamic nationalization.